Low-impedance pole piece and preparation method and application thereof

By using a decentralized agent with zinc ions with a side chain in the lithium -ion battery chip, the electrical conductivity of the polar sheet is improved, the battery power is small, and the higher battery performance and longer service life is achieved.

CN119361695APending Publication Date: 2025-01-24WANXIANG 123 CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411165543.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The high-density electrode plates of lithium-ion batteries have low conductivity and high impedance, which leads to small battery power and difficult to meet the needs of high power.

Method used

A dispersant with zinc ions in the side chain is used, and the polyvinylpyrrolidone main chain and m-phenylenediamine are grafted to form an imine bond to complex the zinc ions and improve the conductivity of the pole piece.

Benefits of technology

A significant increase in the conductivity of the polar sheet, reducing the internal resistance of the battery cells, improving the battery power and charging efficiency, and extending the service life of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005007773460000011
    Figure BDA0005007773460000011
  • Figure BDA0005007773460000012
    Figure BDA0005007773460000012
  • Figure BDA0005007773460000041
    Figure BDA0005007773460000041
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a low-impedance pole piece as well as a preparation method and application thereof. The low-impedance pole piece comprises the following components in parts by weight: 70-90 parts of a positive electrode material; 70-90 parts of a negative electrode material; 40-60 parts of a conductive agent; 55-60 parts of a dispersant; the dispersing agent is composed of a polyvinylpyrrolidone main chain and a side chain which is connected to the main chain and is provided with zinc ions. According to the low-impedance pole piece disclosed by the invention, the conductivity of the pole piece is improved, the resistance is reduced, the power of the battery is improved and the service life of the battery is prolonged by optimizing the formula, adopting the dispersing agent with zinc ions and imine bonds on the side chain and simultaneously adopting a method of overlapping and coating the pole layer and the conductive layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a low-impedance pole piece and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used due to their high energy density, long cycle life, good safety and stability, no memory effect, and environmental friendliness. As the demand for the use of lithium-ion batteries increases year by year, the requirements for their energy density are also getting higher and higher. At present, the energy density of lithium-ion batteries is usually improved by using positive and negative electrode materials with higher gram capacity, reducing the content of binders and conductive agents, and increasing the surface density of electrodes. However, at present, both positive and negative electrode materials are close to the theoretical gram capacity, and it is difficult to continue to improve, and further improvement is likely to damage other properties; due to the reduction in the amount of conductive agent and the increase in the surface density of the electrode, the electronic conductivity of the pole piece becomes worse, the pole piece impedance becomes higher, and the internal resistance of the battery cell is too high, which affects the use of the battery in high-power demand application scenarios. Therefore, in order to meet the needs of use, the field urgently needs to find a lithium battery with high energy density and wide application scenarios. Summary of the invention

[0003] In order to solve the technical problem that the high-density pole piece has low conductivity and high impedance, resulting in low battery power, the present invention provides a low-impedance pole piece and its preparation method and application. The present invention optimizes the formula and uses a dispersant with zinc ions in the side chain, so that the dispersant has good conductivity, improves the conductivity of the pole piece, and thus improves the battery power.

[0004] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a low impedance electrode, comprising the following components in parts by weight: The dispersant is composed of a polyvinyl pyrrolidone main chain and a side chain with zinc ions connected to the main chain, and the structure of the side chain is as follows:

[0005] The present invention adopts a dispersant with zinc ions in the side chain, with polyvinyl pyrrolidone (PVP) as the main body, grafted with the above side chain, and the zinc ions are complexed by the oxygen atoms in the amide bond in the side chain. While maintaining the dispersibility and bonding properties of polyvinyl pyrrolidone, the dispersant can have good electrical conductivity, thereby improving the conductivity of the electrode, so that the battery can be used in high-power demand scenarios. Specifically: the introduction of zinc ions gives the dispersant conductive properties, and at the same time the amide bond has a strong complexing ability for it, so that the zinc ions are attracted and dispersed more evenly and stably in polyvinyl pyrrolidone, reducing agglomeration, and the zinc ions exchange with the metal ions in the conductive material to form stable ion clusters, optimize ion channels, and the covalent bonds (imine bonds) in the structure can enhance the interaction between molecules and promote the migration of charges in the polymer network, thereby enhancing the overall conductivity, and then improving the conductivity of the electrode.

[0006] Preferably, the positive electrode material is selected from at least one of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material, lithium nickel-cobalt-aluminum oxide, lithium nickel oxide and lithium nickel-cobalt-manganese oxide.

[0007] Preferably, the negative electrode material is selected from at least one of graphite, silicon-carbon material and silicon-oxygen material.

[0008] Preferably, the conductive agent is selected from at least one of carbon nanotubes, conductive graphite, conductive carbon black and graphene.

[0009] In a second aspect, the present invention provides a method for preparing a low-impedance electrode, comprising the following steps: 1) mixing the positive electrode material and the negative electrode material with a conductive agent and a dispersant in a solvent to obtain a positive electrode slurry and a negative electrode slurry; 2) Mixing the conductive agent and the dispersant in a solvent to prepare a conductive layer material; 3) First apply a layer of positive electrode slurry or negative electrode slurry, dry it, and then apply a layer of conductive layer material on the current collector, apply at least three layers to obtain a pole piece.

[0010] The number of coating layers can be designed according to actual needs. The present invention effectively fills the gaps between the electrode materials by adding a conductive layer between or on the positive electrode slurry layer and the negative electrode slurry layer, forming a tighter conductive network, which can significantly improve the overall conductivity of the electrode. The multi-layer coating method helps to reduce the resistance between the electrode material and the current collector. The conductive layer acts as a "bridge" to enhance the connection strength between the electrodes, so that the resistance encountered by electrons during the transmission process is smaller. At the same time, the structure provides a smoother transmission channel for lithium ions, thereby reducing the ionic resistance of the battery cell. Due to the increase in conductivity and the reduction in internal resistance, the energy loss of the battery cell during the charging and discharging process is reduced, and the charging and discharging efficiency is improved. In addition, the multi-layer coating method also helps to alleviate the volume change of the battery cell during the charge and discharge cycle, reduce the shedding and pulverization of the electrode material, and thus extend the service life of the battery cell.

[0011] Preferably, in step 1), the preparation method of the dispersant is: polyvinyl pyrrolidone and m-phenylenediamine are mixed in water, and hydrogen peroxide is added to oxidize, hydrochloric acid is added to catalyze, and azobisisobutyronitrile is added to initiate, the product is separated, and is dissolved in isopropanol, and benzoyl chloride, zinc chloride, an amide reaction catalyst and an alkalizing agent are added to react, and purified to obtain the dispersant.

[0012] Polyvinyl pyrrolidone contains carbonyl groups in its structure. After oxidation, the carbonyl groups form aldehyde groups, which generate initial free radicals under the action of initiators. These free radicals will attack the amino groups in meta-phenylenediamine, causing free radical polymerization, and then grafting the meta-phenylenediamine monomer onto the main chain of polyvinyl pyrrolidone. Benzoyl chloride combines with another amino group in meta-phenylenediamine that is not bound to the main chain of polyvinyl pyrrolidone through an amidation reaction, and the oxygen atom in the amide bond forms a coordination bond with the zinc ion, thereby complexing the zinc ion.

[0013] Preferably, the preparation method of the dispersant is specifically as follows: S1: adding polyvinyl pyrrolidone into water to dissolve, then adding m-phenylenediamine, stirring and mixing at 25° C. for 3 to 5 hours to obtain a pre-reaction solution; S2: Add 2-4 mol / L hydrogen peroxide and 2-4 mol / L hydrochloric acid to the pre-reaction solution to catalyze, then add 0.8-4 mol / L azobisisobutyronitrile to initiate, and after complete addition, continue the reaction at 30-80°C for 10-15h, reflux and mature for 1-2h to obtain a graft copolymerization reaction mixture; S3: Add anhydrous ethanol to the graft copolymerization reaction mixture for extraction three times, remove the lower precipitate, dissolve it with isopropanol, add benzoyl chloride and zinc chloride, 5-6 mol / L 4-dimethylaminopyridine as catalyst, 4-6 mol / L potassium carbonate solution as alkalization, continue to react at 60-100°C for 8-12h, add anhydrous ethanol for extraction, remove the lower precipitate, extract it with Soxhlet, dry it, and obtain a dispersant.

[0014] Furthermore, in step S1, the mass ratio of polyvinyl pyrrolidone to meta-phenylenediamine is 1.3 to 3.3:1.

[0015] Furthermore, in step S2, hydrogen peroxide and azobisisobutyronitrile are added dropwise into the pre-reaction liquid.

[0016] Furthermore, in step S2, the molar ratio of hydrogen peroxide to polyvinyl pyrrolidone in the pre-reaction liquid is 1-2:6-15; the molar ratio of hydrochloric acid, azobisisobutyronitrile to m-phenylenediamine in the pre-reaction liquid is 0.6-1.2:0.5-1.3:1.

[0017] Furthermore, in step S3, the mass ratio of benzoyl chloride to zinc chloride is 1 to 1.2:1.

[0018] Furthermore, in step S3, the amount of 4-dimethylaminopyridine added is 15-25 ml, and the amount of potassium carbonate solution added is 40-60 ml.

[0019] Preferably, in step 1), the weight portion of the conductive agent is 6 to 10 parts, and the weight portion of the dispersant is 4 to 6 parts.

[0020] Preferably, in step 1), the solvent used to prepare the positive electrode slurry is N-methylpyrrolidone; and the solvent used to prepare the negative electrode slurry is deionized water.

[0021] Preferably, in step 1), the mixing conditions are: stirring time is 3 to 6 hours, and stirring speed is 500 to 1200 r / min.

[0022] Preferably, in step 2), the solvent used is N-methylpyrrolidone.

[0023] Preferably, in step 2), the mixing conditions are: stirring time is 1 to 3 hours, and stirring speed is 500 to 1200 r / min.

[0024] Preferably, in step 3), the thickness of each layer is 5 to 8 μm.

[0025] Preferably, in step 3), the coating conditions are: coating temperature is 70-130° C., and coating speed is 2-4 m / min.

[0026] Preferably, in step 3), the drying conditions are: the drying temperature is 150-200° C., and the drying time is 5-10 min.

[0027] In a third aspect, the present invention provides an application of the low-impedance electrode in the field of soft-pack batteries.

[0028] Compared with the prior art, the present invention has the following advantages: On the one hand, the present invention optimizes the formula and adopts a dispersant with zinc ions and imine bonds on the side chain, so that the dispersant has good electrical conductivity, improves the conductivity of the electrode, reduces resistance, and increases battery power, so that the battery can be used in high-power demand scenarios; on the other hand, for high-surface-density electrodes, the present invention further improves the conductivity of the electrode and reduces the internal resistance of the battery cell by adopting a multi-layer coating method of stacking a positive / negative electrode layer and a conductive slurry coating layer on the current collector, thereby improving the battery power and charge and discharge efficiency, and at the same time, this method can extend the service life of the battery cell. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the embodiments.

[0030] A low impedance electrode comprises the following components in parts by weight: The dispersant is composed of a polyvinyl pyrrolidone main chain and a side chain with zinc ions connected to the main chain, and the structure of the side chain is as follows:

[0031] As a specific embodiment, the positive electrode material is selected from at least one of lithium iron phosphate, lithium cobalt oxide, nickel cobalt manganese ternary material, lithium nickel cobalt aluminum oxide, lithium nickel oxide and lithium nickel cobalt manganese oxide. The negative electrode material is selected from at least one of graphite, silicon carbon material and silicon oxygen material. The conductive agent is selected from at least one of carbon nanotubes, conductive graphite, conductive carbon black and graphene.

[0032] A method for preparing a low-impedance electrode comprises the following steps: 1) mixing the positive electrode material and the negative electrode material with a conductive agent and a dispersant in a solvent to obtain a positive electrode slurry and a negative electrode slurry; 2) Mixing the conductive agent and the dispersant in a solvent to prepare a conductive layer material; 3) First apply a layer of positive electrode slurry or negative electrode slurry, dry it, and then apply a layer of conductive layer material on the current collector, apply at least three layers to obtain a pole piece.

[0033] As a specific embodiment, in step 1), the preparation method of the dispersant is: polyvinyl pyrrolidone and m-phenylenediamine are mixed in water, and hydrogen peroxide is added to oxidize, hydrochloric acid is added to catalyze, and azobisisobutyronitrile is added to initiate, the product is separated, and is dissolved in isopropanol, and then benzoyl chloride, zinc chloride, an amide reaction catalyst and an alkalizing agent are added to react, and purified to obtain a dispersant.

[0034] As a specific implementation, the preparation method of the dispersant is specifically as follows: S1: adding polyvinyl pyrrolidone into water to dissolve, then adding m-phenylenediamine, stirring and mixing at 25° C. for 3 to 5 hours to obtain a pre-reaction solution; S2: Add 2-4 mol / L hydrogen peroxide and 2-4 mol / L hydrochloric acid solution to the pre-reaction solution for oxidation and then add 0.8-4 mol / L azobisisobutyronitrile for initiation. After complete addition, continue the reaction at 30-80°C for 10-15h, reflux and mature for 1-2h to obtain a graft copolymerization reaction mixture. S3: Add anhydrous ethanol to the graft copolymerization reaction mixture for extraction three times, remove the lower precipitate, dissolve it with isopropanol, add benzoyl chloride and zinc chloride, 5-6 mol / L 4-dimethylaminopyridine as catalyst, 4-6 mol / L potassium carbonate solution as alkalization, continue to react at 60-100°C for 8-12h, add anhydrous ethanol for extraction, remove the lower precipitate, extract it with Soxhlet, dry it, and obtain a dispersant.

[0035] As a specific embodiment, in step S1, the mass ratio of polyvinyl pyrrolidone to m-phenylenediamine is 1.3 to 3.3:1. In step S2, hydrogen peroxide and azobisisobutyronitrile are added to the pre-reaction liquid in a dropwise manner. In step S2, the molar ratio of hydrogen peroxide to polyvinyl pyrrolidone in the pre-reaction liquid is 1 to 2: 6 to 15; the molar ratio of hydrochloric acid, azobisisobutyronitrile to m-phenylenediamine in the pre-reaction liquid is 0.6 to 1.2: 0.5 to 1.3: 1. In step S3, the mass ratio of benzoyl chloride to zinc chloride is 1 to 1.2: 1. In step S3, the amount of 4-dimethylaminopyridine added is 15 to 25 ml, and the amount of potassium carbonate solution added is 40 to 60 ml.

[0036] As a specific implementation, in step 1), the weight of the conductive agent is 6 to 10 parts, and the weight of the dispersant is 4 to 6 parts. In step 1), the solvent used to prepare the positive electrode slurry is N-methylpyrrolidone; the solvent used to prepare the negative electrode slurry is deionized water. In step 1), the mixing conditions are: the stirring mixing time is 3 to 6 hours, and the stirring speed is 500 to 1200 r / min.

[0037] As a specific implementation, in step 2), the solvent used is N-methylpyrrolidone. In step 2), the mixing conditions are: stirring time is 1 to 3 hours, and the stirring speed is 500 to 1200 r / min.

[0038] As a specific implementation, in step 3), the thickness of each layer is 5 to 8 μm. In step 3), the coating conditions are: coating temperature is 70 to 130°C, and coating speed is 2 to 4 m / min. In step 3), the drying conditions are: drying temperature is 150 to 200°C, and drying time is 5 to 10 min.

[0039] Application of the low-impedance electrode in the field of soft-pack batteries. Specific embodiments The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.

[0041] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.

[0042] Example 1 A low impedance electrode, the components and weight proportions of each component are as follows: The method for preparing the low impedance electrode of this embodiment is as follows (the amount of each substance is in parts by weight): (1) Preparation of positive / negative electrode slurry Add 80 parts of lithium iron phosphate, 8 parts of carbon nanotubes, 5 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methylpyrrolidone into a stirrer, stir at 800 r / min for 5 hours to obtain a positive electrode slurry for stand-by use; add 80 parts of graphite, 8 parts of carbon nanotubes, 5 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of deionized water into a stirrer, stir at 800 r / min for 5 hours to obtain a negative electrode slurry for stand-by use.

[0043] (2) Preparation of conductive layer materials 44 parts of carbon nanotubes, 45 parts of meta-phenylenediamine-grafted polyvinyl pyrrolidone and 250 parts of N-methyl pyrrolidone were added into a stirrer and stirred at a speed of 800 r / min for 2 hours to obtain a conductive layer material for standby use.

[0044] (3) Coating The positive electrode slurry is coated on the current collector at a temperature of 100°C and a speed of 3m / min, and then dried at 180°C for 10min. A layer of conductive layer material is coated on the dried positive electrode slurry layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 180°C for 10min. A layer of negative layer material is coated on the dried conductive layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 180°C for 10min to obtain a pole piece.

[0045] The preparation method of the dispersant used in this embodiment is as follows (the amount of each substance is in parts by weight): (1) adding 13 parts of polyvinyl pyrrolidone into water to dissolve, then adding 10 parts of m-phenylenediamine, stirring and mixing at 25° C. for 4 hours to obtain a pre-reaction solution; (2) adding 10 ml of 6 mol / L hydrogen peroxide dropwise to the pre-reaction solution for oxidation, adding 20 ml of 3 mol / L hydrochloric acid solution for catalysis after the addition is completed, leaving it for 2 hours, and then adding 20 ml of 2 mol / L azobisisobutyronitrile dropwise for initiation, and after the addition is completed, continuing the reaction at 50° C. for 12 hours, and refluxing for 2 hours to obtain a graft copolymerization reaction mixture; (3) Anhydrous ethanol was added to the graft copolymerization reaction mixture for extraction three times, the lower precipitate was removed, dissolved with isopropanol, 10 parts of benzoyl chloride and 10 parts of zinc chloride, 25 ml of 5 mol / L 4-dimethylaminopyridine was added for catalysis, and 50 ml of 5 mol / L potassium carbonate solution was added for alkalization. The reaction was continued at 60°C for 12 hours, anhydrous ethanol was added for extraction, the lower precipitate was removed, Soxhlet extraction was performed, and the solution was dried to obtain a dispersant.

[0046] Example 2 A low impedance electrode, the components and weight proportions of each component are as follows: The method for preparing the low impedance electrode of this embodiment is as follows (the amount of each substance is in parts by weight): (1) Preparation of positive / negative electrode slurry 90 parts of lithium iron phosphate, 10 parts of carbon nanotubes, 6 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methylpyrrolidone are added into a stirrer, stirred at 800 r / min for 5 hours, and a positive electrode slurry is obtained for standby use; 90 parts of graphite, 10 parts of carbon nanotubes, 6 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of deionized water are added into a stirrer, stirred at 800 r / min for 5 hours, and a negative electrode slurry is obtained for standby use.

[0047] (2) Preparation of conductive layer materials 40 parts of carbon nanotubes, 43 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methyl pyrrolidone were added into a stirrer and stirred at a speed of 800 r / min for 2 hours to obtain a conductive layer material for standby use.

[0048] (3) Coating The positive electrode slurry is coated on the current collector at a temperature of 100°C and a speed of 3m / min, and then dried at 180°C for 10min. A layer of conductive layer material is coated on the dried positive electrode slurry layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 180°C for 10min. A layer of negative layer material is coated on the dried conductive layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 180°C for 10min to obtain a pole piece.

[0049] The preparation method of the dispersant used in this embodiment is as follows (the amount of each substance is in parts by weight): (1) adding 20 parts of polyvinyl pyrrolidone into water to dissolve, then adding 10 parts of m-phenylenediamine, stirring and mixing at 25° C. for 3 hours to obtain a pre-reaction solution; (2) 10 ml of 5 mol / L hydrogen peroxide was added dropwise to the pre-reaction solution for oxidation, and after the addition was completed, 20 ml of 4 mol / L hydrochloric acid solution was added for catalysis, and the mixture was allowed to stand for 2 h. Then, 20 ml of 4 mol / L azobisisobutyronitrile was added dropwise for initiation. After the addition was completed, the mixture was reacted at 80° C. for 10 h, and refluxed for 2 h to obtain a graft copolymerization reaction mixture; (3) Anhydrous ethanol was added to the graft copolymerization reaction mixture for extraction three times, and the lower precipitate was removed. It was dissolved in isopropanol and 10 parts of benzoyl chloride and 10 parts of zinc chloride were added, 30 ml of 5 mol / L 4-dimethylaminopyridine was used as a catalyst, and 50 ml of 5 mol / L potassium carbonate solution was used for alkalization. The reaction was continued at 100°C for 8 hours, and anhydrous ethanol was added for extraction. The lower precipitate was removed, and Soxhlet extraction and drying were performed to obtain a dispersant.

[0050] Example 3 A low impedance electrode, the components and weight proportions of each component are as follows: The method for preparing the low impedance electrode of this embodiment is as follows (the amount of each substance is in parts by weight): (1) Preparation of positive / negative electrode slurry Add 70 parts of lithium iron phosphate, 6 parts of carbon nanotubes, 4 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methylpyrrolidone into a stirrer, stir at a speed of 1200 r / min for 3 hours to obtain a positive electrode slurry for stand-by use; add 70 parts of graphite, 6 parts of carbon nanotubes, 4 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of deionized water into a stirrer, stir at a speed of 1200 r / min for 3 hours to obtain a negative electrode slurry for stand-by use.

[0051] (2) Preparation of conductive layer materials 28 parts of carbon nanotubes, 47 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methyl pyrrolidone were added into a stirrer and stirred at a speed of 1200 r / min for 1 hour to obtain a conductive layer material for standby use.

[0052] (3) Coating The positive electrode slurry is coated on the current collector at a temperature of 70°C and a speed of 2m / min, and then dried at 150°C for 7min. A layer of conductive layer material is coated on the dried positive electrode slurry layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 150°C for 7min. A layer of negative layer material is coated on the dried conductive layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 150°C for 7min to obtain a pole piece.

[0053] The preparation method of the dispersant used in this embodiment is as follows (the amount of each substance is in parts by weight): (1) adding 33 parts of polyvinyl pyrrolidone into water to dissolve, then adding 10 parts of m-phenylenediamine, stirring and mixing at 25° C. for 6 hours to obtain a pre-reaction solution; (2) 10 ml of 7 mol / L hydrogen peroxide was added dropwise to the pre-reaction solution for oxidation, and after the addition was completed, 20 ml of 2 mol / L hydrochloric acid solution was added for catalysis, and the mixture was allowed to stand for 2 h. Then, 30 ml of 1 mol / L azobisisobutyronitrile was added dropwise for initiation. After the addition was completed, the mixture was reacted at 40° C. for 15 h, and refluxed for 2 h to obtain a graft copolymerization reaction mixture; (3) Anhydrous ethanol was added to the graft copolymerization reaction mixture for extraction three times, the lower precipitate was removed, dissolved with isopropanol, 10 parts of benzoyl chloride and 12 parts of zinc chloride, 15 ml of 6 mol / L 4-dimethylaminopyridine was added for catalysis, and 40 ml of 5 mol / L potassium carbonate solution was added for alkalization. The reaction was continued at 60°C for 9 hours, anhydrous ethanol was added for extraction, the lower precipitate was removed, Soxhlet extraction was performed, and the solution was dried to obtain a dispersant.

[0054] Example 4 A low impedance electrode, the components and weight proportions of each component are as follows: The method for preparing the low impedance electrode of this embodiment is as follows (the amount of each substance is in parts by weight): (1) Preparation of positive / negative electrode slurry Add 80 parts of lithium iron phosphate, 10 parts of carbon nanotubes, 5 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methylpyrrolidone into a stirrer, stir at 500 r / min for 6 hours to obtain a positive electrode slurry for stand-by use; add 80 parts of graphite, 10 parts of carbon nanotubes, 5 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of deionized water into a stirrer, stir at 500 r / min for 6 hours to obtain a negative electrode slurry for stand-by use.

[0055] (2) Preparation of conductive layer materials 44 parts of carbon nanotubes, 45 parts of meta-phenylenediamine-grafted polyvinyl pyrrolidone and 250 parts of N-methyl pyrrolidone were added into a stirrer and stirred at a speed of 500 r / min for 3 hours to obtain a conductive layer material for standby use.

[0056] (3) Coating The negative electrode slurry is coated on the current collector at a temperature of 130°C and a speed of 4m / min. After coating, it is dried at 200°C for 5min. A layer of conductive layer material is coated on the dried negative electrode slurry layer, and the coating temperature and speed are consistent with the negative electrode slurry layer. After coating, it is dried at 200°C for 5min. A layer of positive layer material is coated on the dried conductive layer, and the coating temperature and speed are consistent with the negative electrode slurry layer. After coating, it is dried at 200°C for 5min. The above steps are repeated twice to obtain a pole piece.

[0057] The preparation method of the dispersant used in this embodiment is as follows (the amount of each substance is in parts by weight): (1) adding 13 parts of polyvinyl pyrrolidone into water to dissolve, then adding 10 parts of m-phenylenediamine, stirring and mixing at 25° C. for 3 hours to obtain a pre-reaction solution; (2) adding 10 ml of 6 mol / L hydrogen peroxide dropwise to the pre-reaction solution for oxidation, adding 20 ml of 3 mol / L hydrochloric acid solution for catalysis after the addition is completed, leaving it for 2 hours, and then adding 20 ml of 2 mol / L azobisisobutyronitrile dropwise for initiation, and after the addition is completed, continuing the reaction at 30° C. for 12 hours, and refluxing for 1 hour to obtain a graft copolymerization reaction mixture; (3) Anhydrous ethanol was added to the graft copolymerization reaction mixture for extraction three times, the lower precipitate was removed, dissolved with isopropanol, 10 parts of benzoyl chloride and 10 parts of zinc chloride, 25 ml of 5 mol / L 4-dimethylaminopyridine was added for catalysis, and 60 ml of 5 mol / L potassium carbonate solution was added for alkalization. The reaction was continued at 80°C for 8 hours, anhydrous ethanol was added for extraction, the lower precipitate was removed, Soxhlet extraction was performed, and the solution was dried to obtain a dispersant.

[0058] Comparative Example 1 In this comparative example, polyvinyl pyrrolidone is used as a dispersant to prepare a low impedance electrode, and the components and weight proportions of each component are as follows: The method for preparing the low impedance electrode of this embodiment is as follows (the amount of each substance is in parts by weight): (1) Preparation of positive / negative electrode slurry Add 80 parts of lithium iron phosphate, 8 parts of carbon nanotubes, 5 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methyl pyrrolidone into a stirrer, stir at 800 r / min for 5 hours to obtain a positive electrode slurry for stand-by use; add 80 parts of graphite, 8 parts of carbon nanotubes, 5 parts of polyvinyl pyrrolidone and 250 parts of deionized water into a stirrer, stir at 800 r / min for 5 hours to obtain a negative electrode slurry for stand-by use.

[0059] (2) Preparation of conductive layer materials 44 parts of carbon nanotubes, 45 parts of polyvinyl pyrrolidone and 250 parts of N-methyl pyrrolidone were added into a stirrer and stirred at a speed of 800 r / min for 2 hours to obtain a conductive layer material for standby use.

[0060] (3) Coating The positive electrode slurry is coated on the current collector at a temperature of 100°C and a speed of 3m / min, and then dried at 180°C for 10min. A layer of conductive layer material is coated on the dried positive electrode slurry layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 180°C for 10min. A layer of negative layer material is coated on the dried conductive layer, and the coating temperature and speed are consistent with the positive electrode slurry layer. After coating, it is dried at 180°C for 10min to obtain a pole piece.

[0061] Comparative Example 2 This comparative example adopts a coating method without a conductive layer to prepare a low-impedance electrode, and the components and weight proportions of each component are as follows: The method for preparing the low impedance electrode of this embodiment is as follows (the amount of each substance is in parts by weight): (1) Preparation of positive / negative electrode slurry Add 80 parts of lithium iron phosphate, 8 parts of carbon nanotubes, 5 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of N-methylpyrrolidone into a stirrer, stir at 800 r / min for 5 hours to obtain a positive electrode slurry for stand-by use; add 80 parts of graphite, 8 parts of carbon nanotubes, 5 parts of meta-phenylenediamine grafted polyvinyl pyrrolidone and 250 parts of deionized water into a stirrer, stir at 800 r / min for 5 hours to obtain a negative electrode slurry for stand-by use.

[0062] (2) Coating The positive electrode slurry is coated on the current collector at a temperature of 100°C at a speed of 3m / min, and then dried at a temperature of 180°C for 10min. A layer of negative layer material is coated on the dried positive electrode slurry layer. The coating temperature and speed are consistent with those of the positive electrode slurry layer. After coating, it is dried at a temperature of 180°C for 10min to obtain a pole piece.

[0063] The preparation method of the dispersant used in this comparative example is the same as that in Example 1.

[0064] Comparative Example 3 In this comparative example, a low impedance electrode is prepared, and the components, weight proportions of each component and the preparation method are the same as those in Example 1.

[0065] The preparation method of the dispersant used in this comparative example is as follows (the amount of each substance is in parts by weight): (1) 10 parts of m-phenylenediamine were dissolved in 20% hydrochloric acid solution (mass fraction), mixed with 10 parts of benzoyl chloride dissolved in isopropanol, and then 10 parts of zinc chloride were added. The temperature was maintained at 25° C., and 50 ml of 5 mol / L potassium carbonate solution was added dropwise to obtain a reaction mixture; (2) Anhydrous ethanol is added to the reaction mixture for extraction, and the lower precipitate is removed, washed with water, and dried to obtain the target product.

[0066] (3) 13 parts of polyvinyl pyrrolidone is added to water to dissolve to form a colloidal solution, and the target product is added and mixed to obtain a dispersant.

[0067] Test Example 1 This test example conducts impedance test and electric power test on the performance of low impedance pole pieces prepared in Examples 1-4 and Comparative Examples 1-2. The pole piece impedance is tested in the following manner: two probes are placed on the pole piece to be tested, and the overall resistance value is measured. The electric power is tested in the following manner: the pole piece is made into a battery cell, and the test is performed at a limit rate of 50% SOC 25°C and discharged to 2.7V.

[0068] The following results are obtained: Table 1 Pole impedance performance test results Group Resistance / Ω Limit ratio C Example 1 30.09 61 Example 2 31.45 55 Example 3 30.82 58 Example 4 33.65 51 Comparative Example 1 48.12 31 Comparative Example 2 44.33 34 Comparative Example 3 40.22 43 From Table 1, we can see that: (1) Compared with the electrode sheets prepared in Comparative Examples 1-3, the electrode sheet resistance of Examples 1-4 is significantly reduced and the limiting rate is increased. This shows that the formulation and preparation method of the present invention can reduce the internal resistance of the electrode sheet and increase the battery power. This is because the present invention uses a dispersant with zinc ions and imine bonds in the side chain, and adopts a multi-layer coating method in which the positive / negative electrode layer and the conductive layer are superimposed, which improves the conductivity of the electrode sheet and thus reduces the resistance. Due to the increase in conductivity and the reduction in internal resistance, the energy loss of the battery cell during the charge and discharge process is reduced, the charge and discharge efficiency is improved, and the power is increased.

[0069] (2) The electrode sheet resistance of Example 1 is significantly lower than that of Comparative Example 3, and the limiting ratio is higher than that of Comparative Example 3. This is because the dispersant of Comparative Example 3 is not grafted, while the dispersant of Example 1 is grafted to form an imine bond, which can enhance the interaction between molecules and promote the migration of charges in the polymer network, thereby enhancing the overall conductivity, thereby improving the electrode sheet conductivity; in addition, compared with the dispersant of Comparative Example 3, the main chain of the dispersant of Example 1 is connected by an amide bond, and the oxygen atoms of the amide bond complex the zinc ions, so that the zinc ions are more evenly and stably dispersed in the polyvinyl pyrrolidone, reducing agglomeration, and the zinc ions exchange with the metal ions in the conductive material to form stable ion clusters, thereby optimizing the ion channel.

[0070] Test Example 2 This test example conducts a cycle performance test on the low-impedance electrode sheets obtained in Example 1 and Comparative Example 2, and the test is conducted in the following manner: the electrode sheets are made into battery cells, and at 25°C, they are charged at the maximum charge rate, and discharged at the limit rate, and a full charge and discharge cycle is performed, and the number of cycles in which the battery cell capacity is reduced to 80% of the initial capacity is recorded. The following results are obtained: Table 2 Cycle performance test results Group Number of cycles Example 1 4030 laps Comparative Example 2 3312 laps It can be seen from Table 2 that the number of cycles in Example 1 is significantly higher than that in Comparative Example 2, which indicates that the preparation method of the present invention can extend the service life of the battery cell. This is because the multi-layer coating method helps to alleviate the volume change of the battery cell during the charge and discharge cycle, reduce the shedding and pulverization of the electrode material, thereby extending the service life of the battery cell and further extending the service life of the battery.

[0071] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A low impedance electrode, characterized in that: The composition comprises the following components in parts by weight: The dispersant is composed of a polyvinyl pyrrolidone main chain and a side chain with zinc ions connected to the main chain, and the structure of the side chain is as follows:

2. A low impedance pole piece according to claim 1, characterized in that: The positive electrode material is selected from at least one of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material, lithium nickel-cobalt-aluminum oxide, lithium nickel oxide and lithium nickel-cobalt-manganese oxide.

3. A low impedance pole piece according to claim 1, characterized in that: The negative electrode material is selected from at least one of graphite, silicon-carbon material, and silicon-oxygen material.

4. A low impedance pole piece according to claim 1, characterized in that: The conductive agent is selected from at least one of carbon nanotubes, conductive graphite, conductive carbon black and graphene.

5. A method for preparing a low impedance electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) mixing the positive electrode material and the negative electrode material with a conductive agent and a dispersant in a solvent to obtain a positive electrode slurry and a negative electrode slurry; 2) mixing the conductive agent and the dispersant in a solvent to prepare a conductive layer material; 3) First apply a layer of positive electrode slurry or negative electrode slurry, dry it, and then apply a layer of conductive layer material on the current collector, apply at least three layers, and obtain a pole piece.

6. The method for preparing a low impedance electrode according to claim 5, characterized in that: In step 1), the preparation method of the dispersant is: polyvinyl pyrrolidone and m-phenylenediamine are mixed in water, and hydrogen peroxide is added to oxidize, hydrochloric acid is added to catalyze, and azobisisobutyronitrile is added to initiate, the product is separated, and is dissolved in isopropanol, and then benzoyl chloride, zinc chloride, an amide reaction catalyst and an alkalizing agent are added to react, and purified to obtain the dispersant.

7. The method for preparing a low impedance electrode according to claim 5, characterized in that: In step 1), the weight portion of the conductive agent is 12 to 20 parts, and the weight portion of the dispersant is 8 to 12 parts.

8. The method for preparing a low impedance electrode according to claim 5, characterized in that: In step 1), the solvent used to prepare the positive electrode slurry is N-methylpyrrolidone; the solvent used to prepare the negative electrode slurry is deionized water.

9. The method for preparing a low impedance electrode according to claim 5, characterized in that: In step 2), the solvent used is N-methylpyrrolidone.

10. Application of the low-impedance electrode as claimed in any one of claims 1 to 4 in the field of soft-pack batteries.